2012
DOI: 10.1016/j.jcrs.2011.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Rotational stability of a toric intraocular lens: Influence of axial length and alignment in the capsular bag

Abstract: Toric IOL rotation was greater in eyes with a longer AL. Alignment of the IOL in the capsular bag had no influence on rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 21 publications
8
63
3
4
Order By: Relevance
“…We used slit-lamp photographs to determine the IOL axis, and the mean misalignment of 4.3 degrees was comparable to a previous report [18]. In the current series, the misalignment was not correlated with axial length or corneal diameter; however, Shah et al reported a strong correlation between the axial length and IOL rotation [19]. Although this effect was said to be small and not clinically relevant [5], we experienced spontaneous IOL rotation during aspiration of an ophthalmic viscosurgical device at the end of surgery.…”
Section: Discussionsupporting
confidence: 85%
“…We used slit-lamp photographs to determine the IOL axis, and the mean misalignment of 4.3 degrees was comparable to a previous report [18]. In the current series, the misalignment was not correlated with axial length or corneal diameter; however, Shah et al reported a strong correlation between the axial length and IOL rotation [19]. Although this effect was said to be small and not clinically relevant [5], we experienced spontaneous IOL rotation during aspiration of an ophthalmic viscosurgical device at the end of surgery.…”
Section: Discussionsupporting
confidence: 85%
“…In a recent study, Shah et al 8 report an increased rate of toric IOL rotation with longer ALs. Although the effect was only shown for up to 3 degrees of rotation, and thus the clinical significance is not certain, it may imply that patients with high myopia are at increased risk for postoperative IOL misalignment.…”
Section: Discussionmentioning
confidence: 95%
“…GİL eksen sapmalarının çoğu cerrahi sonrası erken dönemde, 1. hafta ile 1. ay arasında gerçekleşmektedir. 16 GİL aksında cerrahi sonrası 3. ve 4. haftalardan sonra önemli bir eksen sapması görülmemektedir. Bunun 1. ayın sonuna doğru kapsüler kese ön ve arka duvarları arasında yapışıklık gelişmesi ve fibrozise uğrayan kapsüler kese içinde GİLnin hareketinin kısıtlanması ile ilgili olduğu düşünülmektedir.…”
Section: Discussionunclassified